2019
DOI: 10.1002/smi.2867
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in executive functioning and latent herpesvirus reactivation among bereaved and nonbereaved individuals

Abstract: The death of a spouse is a highly stressful event. Better executive functioning has been shown to benefit men to a greater degree than women during stress. We evaluated potential sex differences in stress and immune dysregulation among control and bereaved participants who completed a self-report measure of perceived stress,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Further, when exploring the data, we found that the association between EBV antibody titers (i.e., EBV reactivation, an index of stress‐related immune dysregulation) and perceived somatic symptoms may differ by gender. In a related study, bereaved females demonstrated greater EBV antibody titers than bereaved males (Guevara et al, 2019). If our exploratory findings reflect a gender difference in the true population, this may suggest that although bereaved women have higher EBV antibody titers than men, men may be suffering from the consequences of those elevated titers in the form of somatic symptoms more so than women.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Further, when exploring the data, we found that the association between EBV antibody titers (i.e., EBV reactivation, an index of stress‐related immune dysregulation) and perceived somatic symptoms may differ by gender. In a related study, bereaved females demonstrated greater EBV antibody titers than bereaved males (Guevara et al, 2019). If our exploratory findings reflect a gender difference in the true population, this may suggest that although bereaved women have higher EBV antibody titers than men, men may be suffering from the consequences of those elevated titers in the form of somatic symptoms more so than women.…”
Section: Discussionmentioning
confidence: 92%
“… Researchers suggest relationship satisfaction may play a stronger role in influencing health among married women compared to men (Acitelli, 1992). In addition, bereaved females demonstrated greater EBV antibody titers than bereaved males, in a related study (Guevara et al, 2019). …”
mentioning
confidence: 76%
See 1 more Smart Citation
“…Males had lower EBV antibody titers than females. This finding was correlated with higher male inhibition, or the ability to control and divert attention away from emotion in the presence of stressors [ 184 ]. Figure 3 contains a summary of factors involved in latency and reactivation.…”
Section: Factors Involved In Ebv Reactivationmentioning
confidence: 99%